Air Quality Evaluation of Built Workspace Environments and Antibiotic Sensitivity to Its Staphylococcus Species - Olusola-Makinde, Olubukola Olayemi (European Journal of Applied Sciences, 2026)
The health and wellness of employees can be significantly impacted by the air quality of designed office spaces. The study assessed the microbial, physical and chemical air quality of built environments in Federal University of Technology Akure, Nigeria and sensitivity of associated Staphylococcus species to conventional antibiotics. Air samples were examined for Staphylococcal counts using the settle plate technique and characterized by standard microbiological methods for identification. Physicochemical qualities of studied air samples were determined using standard methods. Bacterial isolates were profiled for antibiotic sensitivity using the disc diffusion technique. Staphylococcal count ranged from 2.4 x 101 to 6.0 x 101 cfu/m3 and 3.8 x 101 to 6.5 x 101 cfu/m3 in air samples of offices with fully air conditioned and offices with open window systems respectively. Presumptive identification confirmed prevalent isolates as Staphylococcus aureus and S. epidermidis. On average, levels of volatile organic compounds, formaldehyde and particulate matter (PM2.5) were higher in air samples of environments with air-conditioned system than environments with open-window system. S. aureus was susceptible to ciprofloxacin (10 µg) at 38.66±3.48 mm zone of inhibition. Findings reveal the presence of Staphylococcus spp. in air samples of built workspace with poor physicochemical qualities. These indicate need for regular monitoring and sanitization so as to mitigate occupation health risks associated with poor air quality.